DEKONSTRUKSI AKUNTANSI: PERAN AKUNTANSI DALAM MEMBANGUN PERADABAN (KRITIK TERHADAP AKUNTANSI TRADISIONAL) - Toni Adhitya; Ruston Nawawi (Istithmar: Jurnal Studi Ekonomi Syariah, 2018)
The new accounting history paradigm in accounting history studies generally criticizes the approach used by traditional accounting history which is said to be ahistorical and antiquated. It is said to be ahistorical because accounting history is written with a present point of view, where accounting history tends to be presented chronologically by slowly displaying current truths. And it is said to be antique because the history of accounting is concentrated on the explanation of "what" happened in the past rather than explaining "how" and "why" accounting affects life. The new accounting history paradigm views accounting not only as a technical tool for recording transactions but as a power and knowledge that can shape human behavior in a community group, which in turn becomes the basis for the establishment of a civilization.